Empowerment for sustainable development - Singh, Naresh (International Institute for Sustainable Development WinnipegCA)
Defines the concepts of empowerment, impoverishment and sustainable development. Identifies a clear causal linkage between the processes of impoverishment and the disempowerment of the peoples and nations of the developing countries. Shows that the processes of impoverishment are not only confined to developing countries, but are also evident in the developed countries.